2018
DOI: 10.2174/1566524018666171219094837
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Helicobacter Pylori-Induced Metabolic Gastrointestinal Dysmotility and Neurodegeneration

Abstract: Helicobacter pylori infection (Hp-I) is a prevalent disorder identified in the majority of the population in many countries around the world and is responsible for substantial gastrointestinal morbidity. Likewise, neurodegenerative diseases such as Alzheimer's disease, Parkinson's diseases, multiple sclerosis or glaucoma defined as ocular Alzheimer's disease, are associated with a large public health burden and are among the leading causes of disability. Emerging evidences suggest that Hp-I may be associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 0 publications
2
33
0
1
Order By: Relevance
“…Moreover, PAR1 is found in specific neuronal populations and glial cells and its activation could induce neurite retraction in olfactory neurons . The latter might promote Hp access brain via the nasal−olfactory pathway which then induces brain pathologies . It is further supported by experimental studies indicating that PAR1‐deficient mice are resistant to neuronal damage and neurologic deficits in a cerebral hypoxia/ischemia model …”
Section: Hp In No‐related Glaucoma Pathophysiologymentioning
confidence: 83%
See 2 more Smart Citations
“…Moreover, PAR1 is found in specific neuronal populations and glial cells and its activation could induce neurite retraction in olfactory neurons . The latter might promote Hp access brain via the nasal−olfactory pathway which then induces brain pathologies . It is further supported by experimental studies indicating that PAR1‐deficient mice are resistant to neuronal damage and neurologic deficits in a cerebral hypoxia/ischemia model …”
Section: Hp In No‐related Glaucoma Pathophysiologymentioning
confidence: 83%
“…Proinflammatory cytokines, such as TNF‐α, are released in Hp ‐I to increase particularly the permeability of the BRB, rendering the retina vulnerable to other harmful agents and contributing to the pathogenesis of glaucoma …”
Section: Hp In No‐related Glaucoma Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…2 Moreover Hp-I is involved in PPI-related disorders discussed by the authors. [1][2][3] The impact of Hp-I with biliary tree diseases has been described.…”
Section: Letter: Helicobacter Pylori In Proton Pump Inhibitor-associamentioning
confidence: 99%
“…Han et al in a cross‐sectional study enrolling 587 elderly participants reported that the highest quartile of anti‐ H. pylori IgG in men was associated with impaired scores on verbal fluency tests ( β = −0.38; OR: 3.01; 95% CI: 1.42, 6.38), while no association was found with global cognition. Some authors also investigated the potential role of H. pylori in neurodegeneration by hypothesizing different pathogenic mechanisms, including a potential effect in tau phosphorylation . Nevertheless, an animal study by Zhou et al did not show any role of H. pylori in changing Thr205, Th3231, Ser396, and Ser404 sites in the hippocampus and cerebral cortex, which are typical markers of Alzheimer's disease …”
Section: Neurologic Diseasesmentioning
confidence: 99%